2011
DOI: 10.1007/s11284-011-0857-9
|View full text |Cite
|
Sign up to set email alerts
|

Tiller hierarchy and defoliation frequency determine bud viability in the grass Poa ligularis

Abstract: Bud viability after various defoliation frequency treatments was determined in the perennial bunchgrass Poa ligularis under arid field conditions from 2002 to 2005. Bud respiratory activity was examined on various stem base hierarchies using the tetrazolium test, as validated with the vital stain Evan's blue. The hypothesis of this work was that the total and viable axillary bud numbers on stem bases of all study stem base hierarchies are reduced as defoliation frequency increases. Interpretation of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, P. ligularis ecotypes from sites with different grazing histories in the Patagonian steppe only partially compensate for an equal proportion of biomass removed (Rotundo and Aguiar, 2008). Other studies (Klich et al, 1996;Busso et al, 2011) have also demonstrated the sensitivity of P. ligularis to defoliation. Less is known about the response to defoliation of S. clarazii, although this mid-tall perennial grass presents low tiller density and a relatively low production of seeds per plant (Distel and Klich, 1996), which may limit its regrowth capacity and seedling recruitment under heavy grazing.…”
Section: Species Replacementmentioning
confidence: 90%
“…Similarly, P. ligularis ecotypes from sites with different grazing histories in the Patagonian steppe only partially compensate for an equal proportion of biomass removed (Rotundo and Aguiar, 2008). Other studies (Klich et al, 1996;Busso et al, 2011) have also demonstrated the sensitivity of P. ligularis to defoliation. Less is known about the response to defoliation of S. clarazii, although this mid-tall perennial grass presents low tiller density and a relatively low production of seeds per plant (Distel and Klich, 1996), which may limit its regrowth capacity and seedling recruitment under heavy grazing.…”
Section: Species Replacementmentioning
confidence: 90%
“…The effects of grazing on the regrowth of palatable native grasses in semi-arid grasslands of Patagonia (Argentina) have been widely studied (e.g., Graff et al 2007;Gittins et al 2010;Busso et al 2011). Although palatable species can tolerate defoliation better than unpalatable species , high grazing pressure may nevertheless threaten their populations (León and Aguiar 1985;Gaitán et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It was unclear why the increase in G was accompanied by the decrease in U in A. cristatum, but it may relate to the limitation of the number of tillers produced: successive tiller production by the development of axillary buds allows persistent biomass production of perennial grasses (Flemmer et al 2002;Jewiss 1972), and therefore, tiller number commonly correlates positively with aboveground biomass (Boe 2007;Boe and Beck 2008;Boe and Casler 2005;Zarrough et al 1983). In perennial grasses, the number of buds and tillers remains almost constant even after repeated clipping (Busso et al 1989(Busso et al , 2011, which is likely to be the case in our two species. Thus, in A. cristatum, the regrowth of aboveground biomass may be limited by the number of tillers, and consequently U may have decreased with the increase in G. The decrease in U would thus contribute to the growth of belowground parts, including rhizomes (Bai et al 2010;Wan et al 2011).…”
Section: Discussionmentioning
confidence: 99%